MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN MELALUI TEKS BACAAN DENGAN MODEL COOPERATIVE INTEGRATED READING AND COMPOSITION KELAS IV - Samaun, Deys Safitri; Pateda, Lamsike; Talango, Siti Rahmawati (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
This study aims to determine whether the Cooperative Integrated Reading And Composition Model can improve the reading comprehension skills of fourth grade students at SDN 1 Pinogu. This type of research is classroom action research. The subjects of this study were 17 fourth grade students at SDN 1 Pinogu. The data analysis techniques used in this study were test result analysis and observation result analysis. Based on the results of the study, it can be concluded that learning Indonesian using the Cooperative Integrated Reading And Composition learning model can improve the reading comprehension skills of fourth grade students at SDN 1 Pinogu. This is indicated by the learning outcomes of students in cycles I and II which have increased. In cycle I, there were 10 students categorized as achieving KKM with a percentage of 59% and in cycle II, there were 15 students categorized as achieving KKM with a percentage of 88%. So KKM increased by 12%. This is because in cycle II students have started to improve in the learning process, most students have maximized their reading comprehension. So student learning in cycle II has reached the KKM value or the performance indicator that has been set. Thus, the hypothesis in this study using the Cooperative Integrated Reading and Composition learning model can improve the reading comprehension skills of fourth grade students at SD Negeri 1 Pinogu.